2020
DOI: 10.1177/0004563220982325
|View full text |Cite
|
Sign up to set email alerts
|

Survey of patient perception of pre-analytical requirements for blood testing in the UK and RoI

Abstract: Background A patient survey developed by the Pre-Analytical Phase Special Interest Group of the Association for Clinical Biochemistry and Laboratory Medicine (ACB-PA-SIG) was conducted during November and December 2019. The survey aimed to determine the quality of information provided to patients in preparation for their blood test(s). In addition, the ACB-PA-SIG provide a number of recommendations, which, if adopted, may yield higher quality test results and improve patient management. Methods The survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Nevertheless, it is always important to know the fasting status of the patient and interpret the results accordingly. It is also important to note that patients may not be fully aware of the significance of fasting or may not be well informed about the requirement to fast ( 7 - 9 ). We identified this step as error-prone, and similar error frequencies have been reported in other European countries ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is always important to know the fasting status of the patient and interpret the results accordingly. It is also important to note that patients may not be fully aware of the significance of fasting or may not be well informed about the requirement to fast ( 7 - 9 ). We identified this step as error-prone, and similar error frequencies have been reported in other European countries ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These limitations could introduce a potential source of selection bias and limit the generalisability of the findings to the entire population of specialists in the country. Nevertheless, questionnaires are a widely used method to assess compliance with various guidelines or recommendations, as well as to gather information on compliance with guidelines for VBS ( 1 , 5 , 7 , 9 , 12 , 27 , 28 ). Another method that could be used for this purpose is observation studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that only a minority of the patients tend to arrive well-prepared for blood sample collection [23,29,35], and this is no exception in Lithuania [26]. The reasons for this trend could be several.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that patients often present for laboratory tests ill-prepared [23][24][25][26]. Multiple factors contribute to this lack of preparation, including variations in preparation recommendations from different laboratories [8,27,28] and patient attitudes towards the significance of preparation for laboratory testing [29]. Additionally, the attitude of non-laboratory healthcare professionals regarding the importance of patient preparation for laboratory testing can be another influential factor affecting the quality of patient preparation.…”
Section: Introductionmentioning
confidence: 99%